Review of Middle East Economics and Finance (De Gruyter, 2003)
The Review of Middle East Economics and Finance (RMEEF) addresses applied original research in the fields of economics and finance pertaining to the MENA region (Middle East and North Africa), including Turkey and Iran. The journal also publishes articles that deal with the economies of neighboring countries and/or the relationship and interactions between those economies and the MENA region.